Does Institutional Ownership Moderating Tax Avoidance? An Empirical Analysis In Indonesian List Company - Nela Dharmayanti; Yosi Safri Yetmi; Anna Sofia Atichasari; Aisyah Ratnasari; Feni Fitriyani (Universitas Serang Raya, 2024)
This study aims to determine the effect of Thin Capitalization, Transfer Prices, and Profitability on Tax Avoidance and the role of institutional ownership in moderating it. The population used in this study is LQ45 companies listed on the IDX, using a purposive sampling technique. The number of samples is 11 companies with financial statement data collection for the 2016-2020 period. This study uses a quantitative method, with SPSS version 23.0, to test the analysis. The results show that Thin Capitalization has a positive and significant effect on Tax Avoidance, with the value of t count > t table (2.246>2.00665). Transfer prices have a positive and significant effect on Tax Avoidance with a value of t count > t table (3.121>2.00665). Profitability partially has a positive and significant effect on Tax Avoidance with a value of t count > t table (6.211>2.00665). Thin Capitalization, Transfer Prices, and Profitability simultaneously positively and significantly affect Tax Avoidance with the calculated F value> F table (74.719>2.55). However, Institutional Ownership does not moderate the relationship between Thin Capitalization, Transfer Prices, and Profitability on Tax Avoidance